Age-Appropriateness of Porcine Models Used for Cell Transplantation. Issue 2 (February 2019) - Tohyama, Shugo; Kobayashi, Eiji
Pigs have traditionally been used for preclinical experiments, and body size-matching is important for cell therapy in animal models used for preclinical trials. It has been shown that the efficacy of the transplanted cells is dependent on the response of the host heart and the age of experimental pigs.